Cross-Cultural Comparisons of the Factors Influencing the High Reading Achievement in Turkey and China: Evidence from PISA 2018 - Kilic Depren, Serpil; Depren, Ozer (SPRINGER HEIDELBERG, 2022)
The motto if you can't measure it, you can't manage it is the basic idea of innovation in every area of business life. In education, governments get involved in many studies such as the Programme for International Educational Study (PISA), which can lead policy-makers on how to measure and improve the level of education. This research focuses on determining factors that have a significant impact on the high level of achievement of students using the most recent PISA study held in 2018. With this aim, the Activity Region Finder algorithm, which is not used in the educational area in the literature, is performed for both Turkey and China. The result of Turkey is compared to China which is the best-performer country in PISA 2018. As a result of this research, metacognition competencies and the socio-economic and cultural status of students are statistically significant factors for both Turkey and China.
Keywords: Activity region finder; Reading literacy; Meta-cognition ability; PISA; Cross-country analysis; Subject classification codes; C14; C38; I21; Education & Educational Research